Likovni kurikul – primerjava konceptov v luči prenove učnega načrta za likovno vzgojo (2008) - Zupančič, Tomaž (Revija za elementarno izobraževanje, 2008)
Art Education Curricula – A Comparison of the Concepts Involved in Renovating the Teaching Plan for Art Education. The article gives some of the basic changes that have been made to the Slovenian visual art curriculum. These changes are then juxtaposed with actual contemporary theories in art education. We made a conceptual comparison between open and closed art curricula. We then compared different visual art curricula by analysing their differences, faults and importance. We put stress on the influence governments have on decisions made concerning closed art curricula and whether aspirations for political control are involved. We then give reasons for advocating the implementation of an open art curriculum. The article also includes an interpretation of the changes in content and structure that have been made to the visual artcurriculum.
Keywords: art education; visual art didactics; art curriculum; post-modern curriculum